Developing critical thinking through critical reading in the literature classroom - Mohd. Asraf, Ratnawati; Muhamad, Ainon Jariah; Supian, Nadya (American Scientific Publishers, 2017)
Islam places strong emphasis for Muslims to seek for knowledge and for them to think and reflect. This paper discusses the importance of seeking knowledge in Islam and the importance of critical thinking in the quest for knowledge. It also discusses the critical and analytical thinking ability of Malaysian students and graduates, and the need to teach critical thinking in Malaysian schools. Further, it proposes that critical thinking be taught through critical reading and how this would best be achieved in the Literature classroom. © 2017 American Scientific Publishers All rights reserved.